Considerations for employing intersectionality in qualitative health research - Abrams, Jasmine A.; Tabaac, Ariella; Jung, Sarah; Else-Quest, Nicole M. (Social science & medicine (1982), 2020)
Intersectionality theory has recently emerged in the health sciences as a critical theoretical and methodical approach. Though some scholars have outlined explicit guidelines for applying intersectionality in research using quantitative methods, others have cited epistemological concerns and additive thinking to advocate for the analysis of intersectionality with qualitative methods. Thus, there remains a need for additional guidance and support for utilizing and applying intersectionality theory throughout the qualitative research process. With the goal of demystifying the process of utilizing intersectionality as a methodological approach in qualitative research in the health sciences, this paper provides researchers with recommendations, specific examples, and important considerations for incorporating intersectional approaches into study conceptualization, participant recruitment, data collection, and data analysis. Additionally, this paper reviews challenges that researchers may experience in conducting research using intersectional approaches and offers suggestions for overcoming challenges. This paper offers timely and relevant information that can be used to strengthen the theoretical and methodological rigor of qualitative health research, especially studies that seek to advance health equity. •Intersectionality holds researchers accountable for critical inquiry in the research process.•Intersectionality has implications for study design, sampling, data collection, and analysis.•Through intersectionality, we can generate new knowledge to advance health equity.